2022
DOI: 10.1177/09722629221096050
|View full text |Cite
|
Sign up to set email alerts
|

Green Trade Credit and Sustainable Firm Performances During COVID-19: A Conceptual Review

Abstract: The modernization of the economic world creates environmental issues around the globe, to improve global problems such as global warming, inequality, climate change, hunger and poverty; it is necessary to improve sustainable performance. Mostly, the product manufacturers have a greater influence on the supply chain and the environment. Before COVID-19, the economy of Pakistan was belligerent but not collapsed; however, COVID-19 created a situation where most of the companies will go bankrupt. Pakistan is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…For enhancing a firm’s performance firms must adopt green practices (such as green processes, green design, and green technology). Many empirical studies showed that firms having concerned about their environment helps in improving their firm performance and fostering sustainable developments (Svensson et al 2016 ; Fahim and Mahadi 2022 ). A negative association was also found between green supply chain management practices and economic performance; therefore, there is a need to further investigate the green supply chain management practices to encourage firms to achieve firm sustainability (Khan et al 2021 ).…”
Section: Key Results and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For enhancing a firm’s performance firms must adopt green practices (such as green processes, green design, and green technology). Many empirical studies showed that firms having concerned about their environment helps in improving their firm performance and fostering sustainable developments (Svensson et al 2016 ; Fahim and Mahadi 2022 ). A negative association was also found between green supply chain management practices and economic performance; therefore, there is a need to further investigate the green supply chain management practices to encourage firms to achieve firm sustainability (Khan et al 2021 ).…”
Section: Key Results and Findingsmentioning
confidence: 99%
“…A negative association was also found between green supply chain management practices and economic performance; therefore, there is a need to further investigate the green supply chain management practices to encourage firms to achieve firm sustainability (Khan et al 2021 ). Sustainable firm performance helps businesses in creating the values and obtaining the shareholder objectives, by executing opportunities and managing the threats that originate from social, economic, and environmental development (Fahim and Mahadi 2022 ).…”
Section: Key Results and Findingsmentioning
confidence: 99%